Two independent allohexaploidizations and genomic fractionation in Solanales - Zhang, Yan; Zhang, Lan; Xiao, Qimeng; Wu, Chunyang; Zhang, Jiaqi; Xu, Qiang; Yu, Zijian; Bao, Shoutong; Wang, Jianyu; Li, Yu; Wang, Li; Wang, Jinpeng (Frontiers in Plant Science, 2022)
Solanales, an order of flowering plants, contains the most economically important vegetables among all plant orders. To date, many Solanales genomes have been sequenced. However, the evolutionary processes of polyploidization events in Solanales and the impact of polyploidy on species diversity remain poorly understood. We compared two representative Solanales genomes (Solanum lycopersicum L. and Ipomoea triloba L.) and the Vitis vinifera L. genome and confirmed two independent polyploidization events. Solanaceae common hexaploidization (SCH) and Convolvulaceae common hexaploidization (CCH) occurred ~43–49 and ~40–46 million years ago (Mya), respectively. Moreover, we identified homologous genes related to polyploidization and speciation and constructed multiple genomic alignments with V. vinifera genome, providing a genomic homology framework for future Solanales research. Notably, the three polyploidization-produced subgenomes in both S. lycopersicum and I. triloba showed significant genomic fractionation bias, suggesting the allohexaploid nature of the SCH and CCH events. However, we found that the higher genomic fractionation bias of polyploidization-produced subgenomes in Solanaceae was likely responsible for their more abundant species diversity than that in Convolvulaceae. Furthermore, through genomic fractionation and chromosomal structural variation comparisons, we revealed the allohexaploid natures of SCH and CCH, both of which were formed by two-step duplications. In addition, we found that the second step of two paleohexaploidization events promoted the expansion and diversity of β-amylase (BMY) genes in Solanales. These current efforts provide a solid foundation for future genomic and functional exploration of Solanales.